Investigation of Fasciola hepatica seroprevalence in Elazi? region - Kaplan, Mustafa; Kuk, Salih; Kalkan, Ahmet; Demirda?, Kutbettin; Özdarendeli, Aykut (My University, 2002)
In this study, for the detection of Fasciola hepatica infection seroprevalence in Elazi? region (Eastern Anatolia), the presence of F.hepatica IgG antibodies were investigated by using a home-made enzyme immunoassay, in the sera of 540 healthy volunteers (254 males, 286 females) from different age groups (age range: 0-81 yrs, mean age: 33±20 yrs). The total seropositivity rate in this region of our country was found 2.78%, with no differences between males and females (respectively, 2.76% and 2.8%). F.hepatica IgG positive subjects were then evaluated for the parameters of age, educational and socioeconomical status, and it was found that there were no statistically significant differences.
Elazi? yöresi?nde Fasciola hepatica seroprevalansinin araştirilmasi
Keywords: Fasciola hepatica; Seroprevalence